2019
DOI: 10.3390/su11061768
|View full text |Cite
|
Sign up to set email alerts
|

The Environmental Effects of Urban Development in Hanoi, Vietnam from Satellite and Meteorological Observations from 1999–2016

Abstract: Since 1990 the Hanoi capital region (or Hanoi metropolitan area) in Vietnam has undergone rapid development, which has gone together with increasing socio-economic growth and prosperity. However, the environmental degradation that has accompanied urban development has raised considerable concern from the public in recent years. This research investigates the effects of urban development on urban sprawl, urban heat island (UHI), and metropolitan weather phenomena that are related to the quality of urban life in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 31 publications
4
32
0
1
Order By: Relevance
“…The theoretical LST data implemented into model (1) should be compared to direct LST observations in order to justify their use to define and develop spatial planning policies aimed at decreasing LST and at mitigating its negative impacts on urban and rural areas. A clear-cut and straightforward validation methodology is described and applied by Nguyen et al in a recent article concerning Hanoi [1]. Secondly, at present, the Sardinian municipalities and the regional administration seem very far from understanding the potential of policies geared towards decreasing LST, such as urban green and blue grids, green roofs and facades, and afforestation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The theoretical LST data implemented into model (1) should be compared to direct LST observations in order to justify their use to define and develop spatial planning policies aimed at decreasing LST and at mitigating its negative impacts on urban and rural areas. A clear-cut and straightforward validation methodology is described and applied by Nguyen et al in a recent article concerning Hanoi [1]. Secondly, at present, the Sardinian municipalities and the regional administration seem very far from understanding the potential of policies geared towards decreasing LST, such as urban green and blue grids, green roofs and facades, and afforestation.…”
Section: Discussionmentioning
confidence: 99%
“…Fast changes aimed at promoting social and economic development have characterized international land cover dynamics in the last few decades [1,2]. Land cover features are related not only to rapid urbanization, but also to processes of higher anthropization, such as the transformation of forest areas into agricultural areas or transitions from woodlands and shrubs to new predominantly homogeneous agrarian areas [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Environmental problems occur in many countries, such as India (Bhattacharyya et al, 2015), China (Aregay, Zhao, Li, Xia, & Chen, 2016), Vietnam (Nguyen, Lin, & Chan, 2019), and Indonesia. One city that has environmental problems in Indonesia is Bandung (Septian, Ruhimat, & Somantri, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies [8][9][10][11] have shown that built environment factors or urban physical characteristics such as population density, building cover ratio, floor area ratio, and anthropogenic heat, can significantly affect the UHI intensity. The population density can show the concentration and distribution of the urban population and the urbanization intensity within a city [9] and be used as a metric to determine spatial variation in electrical use and thus estimate energy consumption and the magnitude of anthropogenic heat in a city [9,20].…”
Section: Analysis Of the Built Environment Factorsmentioning
confidence: 99%
“…The effects were investigated of urban development in a tropical area on urban sprawl, the urban heat island (UHI) effect, and metropolitan weather phenomena that are related to the quality of urban life in the Hanoi metropolitan area in Vietnam. The results imply that during the study period from 1999 to 2016, urban development and its environmental effects have imposed pressing issues and new challenges for sustainable development [10]. From the 2000-2015 Bangkok survey, it was found that urban physical characteristics have a significant impact on the UHI magnitude, particularly the floor area ratio (FAR) and building coverage ratio (BCR), in which temperature levels at 10 p.m. and the thermal cooling rate between 4 and 10 p.m. had a correlation value (r) of over 0.50 [11].…”
Section: Introductionmentioning
confidence: 96%